Multi control adaptive fractional order PID control approach for PV/wind connected grid system. (3rd February 2021) - Sibtain, Daud; Murtaza, Ali F.; Ahmed, Naveed; Sher, Hadeed Ahmed; Gulzar, Muhammad Majid
Summary: This paper introduces a novel genetic optimize multi‐control adaptive fractional order PID (AFOPID) for Photovoltaic (PV) and Wind connected grid system. The proposed AFOPID controller is optimized by a genetic algorithm (GA) to initialize the controller parameters. The renewable energy sources are mathematically modeled using multi control approach (MCA). In the proposed work, the MCA involves the maximum power point tracking (MPPT), dc link voltage, and current control and quadrature axis modeling. Furthermore, the current control functionalities are performed through an adaptive approach of AFOPID, where the controlling parameters are updated by measured error at every instant. The idea behind the research is to improve the tracking efficiency by introducing better control in order to gain maximum power from the source with minimized total harmonic distortion (THD). The proposed control scheme is tested using computer‐aided experimentation by varying the output of renewable energy sources, inverter uncertainty, and grid voltage variations. The results are benchmarked against the conventional fuzzy logic controllers, fractional‐order PID, and PI controllers. Moreover, to evaluate the effectiveness of the proposed controller, the MCA‐AFOPID is compared with ant colony optimization (ACO) and particle swarm optimization (PSO) optimized FOPID controller respectively. The proposed controller outperforms as compared to other controller. Abstract : This paper has proposed an efficient method in dealing with the pivotal requirements for a renewable connected grid system. A multi‐control adaptive fractional (MCA‐AFOPID) controller is proposed to control the inverter properties for achieving high efficiency with low computations. Genetic algorithm is applied to optimize FOPID controller in proportion to an error. Robustness of MCA‐AFOPID controller is emphatic from its critical parameters achievements and low THD.